(untitled) (Eurasian Journal of Ecology, 2016)
Results of studying of intraspecific variability Populus diversifolia Schrenk. on the example of 6 morfologo-biometric indicators of growth (height, diameter of a circle of krone and a trunk, length, width and quantity of cloves on a sheet plate) are given on the basis of which the conclusion about a high polimorfical and ecological plasticity of this rare species in the conditions of a desert zone of Mangistau area are drawn.